RIMBA Fashion Art Show - Mohamad Faizuan, bin Mat (2019)
Saradise Gallery proudly present "Rimba, Saradise Evenings" Fashion Exhibition. A community event organized and hosted by Saradise Gallery to showcase a collaborative efforts to unite the artistic creations from various Sarawak Artists with local Sarawak Fashion Designers to create and transform art on canvas into fashionable pieces using “Rimba” or nature as its theme for inspiration.